BODIPY-containing porous organic polymers for gas adsorption. (3rd October 2016) - Xu, Yunfeng; Chang, Dan; Feng, Shi; Zhang, Chong; Jiang, Jia-Xing
Abstract : BODIPY-containing microporous organic polymers were synthesized via a Sonogashira–Hagihara coupling reaction of a BODIPY derivative and a range of aryl–alkyne monomers. Abstract : A series of BODIPY-containing microporous organic polymers was synthesized via a Sonogashira–Hagihara cross-coupling reaction of a BODIPY derivative with triple polymerisable groups and a range of aryl–alkyne monomers. All of the polymers show high isosteric heats of CO2 adsorption (23.3–27.3 kJ mol −1 ) because the incorporation of heteroatoms (N, B, F) from the BODIPY unit into the polymer skeleton enhanced the binding affinity between the pore wall and CO2 molecules. The aryl–alkyne monomer has a large influence on the surface area and CO2 adsorption performance of the resulting polymers. The polymer BDPCMP-3 shows a high Brunauer–Emmett–Teller specific surface area of up to 725 m 2 g −1, while BDPCMP-2 with a low surface area of 582 m 2 g −1 shows a high CO2 uptake ability of 2.25 mmol g −1 at 1.13 bar/273 K with a CO2 /N2 adsorption selectivity of 32.3.